1986
DOI: 10.1111/j.1744-7348.1986.tb03222.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in peel pigmentation during ripening of mango fruit (Mangifera indica var. Tommy Atkins)

Abstract: SUMMARYThe pigments in the peel of Tommy Atkins mango were analysed at six stages during ripening at 22 oC. The loss of green colour and the development of yellow colouration was associated with an almost complete loss of chlorophyll and an increase in carotenoids. Anthocyanin content showed a slight decrease during ripening. An ultrastructural study showed plastids in green fruit with a well developed grana network system. On ripening the chloroplasts underwent extensive disorganisation which was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 16 publications
6
52
0
2
Order By: Relevance
“…However, the storage period did not affect the variability of the measured data. Medlicott et al (1986) reported a decrease in anthocyanin during storage. The results of the current study differ from the previous report.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the storage period did not affect the variability of the measured data. Medlicott et al (1986) reported a decrease in anthocyanin during storage. The results of the current study differ from the previous report.…”
Section: Resultsmentioning
confidence: 99%
“…This result differed from the trends observed for anthocyanin and SSC. However, Medlicott et al (1986) reported that chlorophyll decreases during postharvest ripening. Therefore, the trends shown in Fig.…”
Section: Prediction Model For Anthocyanin Concentration and Sscmentioning
confidence: 99%
See 2 more Smart Citations
“…b-Carotene, xanthophyll esters and xanthophylls are the principal carotenoids in the peel of mango fruit (Lizada 1993). The carotenoid level in skin increases during ripening with a gradual decrease in the anthocyanin in 'Tommy Atkins' mangoes (Medlicott et al 1986a). Anthocyanidin hexoside, quantified as peonidin-3-O-glucoside, has been tentatively identified as a major anthocyanin in skin of red coloured mango cultivars (Berardini et al 2005) which is in contrast to peonidin-3-galactoside reported previously (Proctor & Creasy 1969).…”
Section: Colourmentioning
confidence: 46%